Generation and analysis of expressed sequence tag sequences from a soft‐seeded pomegranate cDNA library. (11th October 2017) - Zhang, Shuiming; Chen, Lei; Huang, Rong; Isha, Abdurazak; Dong, Lili
Abstract: The cultivation of soft‐seeded pomegranate is an important direction in pomegranate breeding. To comprehensively understand the molecular mechanisms involved in the formation of soft‐seeded pomegranate ( Punica granatum . var. Hongmanaozi), we established an expressed sequence tag (EST) resource. Two thousand valid sequences were generated, from which 907 unigenes were obtained after initial assembly using theclustalx program. Among these unigenes, 51 showed no similarity to any protein in the public databases, 433 matched with proteins of unknown function, and 423 matched with proteins of known or putative functions. The 423 unigenes were further classified into 13 categories. Among these categories, protein synthesis, cell structure, protein destination and storage, secondary metabolism, signal transduction and transporters accounted for 8%, 8%, 4%, 7%, 6% and 17%, respectively. We also successfully developed 10 highly polymorphic expressed sequence tag‐simple sequence repeat (EST‐SSR) markers for pomegranate. The results provide a new tool for future activities in pomegranate breeding.